(3TQM GdCSHGH hGdYdGeGJs - (3GdcQeGfj, HQgGf GdOjf, fajS Hf YhV Hf Mcje GdcQeGfj, HQgGf GdOjf, J HYO (B841(3g` (B1438(3es ((3eMeO egOj Hf eMeO HGbQ GdNhFjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B,,, (3bGd GdeUfa(B: (3GdUOGY Cde, hgh NQhL ef MGd WHjYjI Edi MGd ZjQ WHjYjI Ydi eG YQaI LGdjfhS hef JHYg cGdQGRjs
(3BNQgG (B:s
(3BNQgG(B: (3hjYWi ef GdRQGhfO GdWhjd hGdNHWGjG hbThQ CUd GdcHQ hObjb GdcQSfI CLRGA ShGA HGdTQGH Ch HeGA GdYSd hRgQI (B.. (3ef JQjGbGJg hQHeG Hbj ajg GSJYeGd GdedM hGdNd Ydi ehVY GdYVI(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 44s
(3cTa GdXfhf, L (B1: 77s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs